PROPOSED STRATEGY FOR BUSINESS TO BUSINESS MARKETING OF INDONESIA TELECOMMUNICATION INDUSTRY COMPANY - WIMA ADITYA M (NIM : 29108324); Pembimbing Akademik : Ir. Evo S. Hariandja, MM, SITI
Indonesia Telecommunication Industry Company is one of State owned companies that engaged in providing tools and services of telecommunication infrastructures. The company has improved the business orientation from pure manufacture to solution system based industry, particularly in the field of information and communication system and integrated technology. Business issues faced by Indonesia Telecommunication Industry Company is the decrease of annual selling rate and the percentage of selling growth which influence the growth of the company and even determine the live of the company. The decrease of selling rate is mainly due to the selling rate is not competitive. The first reason is that the company buys raw material in a very high price in country or import. Secondly, there are so many competitors. Besides, there are some other reasons to be considered. The problem above should be solved immediately by having evaluation and re-design marketing strategy to increase selling rate and meet the target. Based on problems above, it is recommended to carry out business issue exploration by using internal and external analysis. The approach used as the basic of marketing strategy is conditional strategy analysis which consists of business marketing analysis, PorterÃ‚Â’s 5 forces, SWOT, Market Analysis, Political Legal Environment and Marketing Mix. SWOT Analysis shows that the company has good experience in system and telecommunication tools industry as well as has great capital available. However, the activity of marketing mix is not optimal and ineffective. Therefore, it is recommended to improve activity of marketing mix. Some efforts carried out by the company to meet the target are maintaining the quality of the product, increasing the features of the product based on customers need, providing competitive price, having effective promotion, increasing employees ability, and improving working process as well as customers complaint. The solution will be directly implemented by the company within one year and will be evaluated to see the result of the marketing strategy.